Impact and Law Enforcement of Vigilante in the Society - Margareta, Veronica Sherly; Waspiah, Waspiah (Jurnal Scientia Indonesia, 2020)
This study aims to determine: the meaning of vigilante action or eigenrechting, the impact that can be caused by vigilante action and, law enforcement against vigilante action in society. This research is included in the type of qualitative research which is a literature study (Library Research) which uses journals as reading references. The method used is descriptive analysis by providing clear, objective, systematic, analytical and critical descriptions and information regarding the impact and law enforcement of self-play in the community. The data used in this study is secondary data whose material is sourced from legal journals. The act of vigilantism is a translation of the word from the Dutch language, namely "Eigenrichting" which is defined as a way of taking vigilantes which is carried out by taking rights without heeding applicable laws, without the knowledge of the government and without the use of tools on the government's power. Violence often coexists with violations of the rights of others. Acts of vigilantism can have an impact on many parties such as victims of mis-targeting, perpetrators of crimes who are victims, the community, crime rates, even those who take part in taking vigilante action are also affected by their actions which can be punished according to their actions. what he has done. Punishments that can ensnare perpetrators of vigilante action have been regulated in the Criminal Code, namely Article 170 of the Criminal Code which regulates legal sanctions for perpetrators who commit acts of violence against people or goods in public, Article 351 of the Criminal Code regarding acts of persecution and Article 55 of the Criminal Code regarding participating in acts of violence. and in doing an action.